DAMPAK KEBIJAKAN INTERNATIONAL TRIPARTITE RUBBER COUNCIL TERHADAP EKSPOR KARET ALAM INDONESIA - Arkan Fairuzo (2022)
This study aims to discuss the impact of the International Tripartite Rubber Council (ITRC) policy on Indonesia's natural rubber exports using the regime of international theory and the international political economy. The method used is descriptive qualitative by using primary data sources and secondary data. Data collection techniques using interviews, observation, and documentation. Researchers used the stages of data empathy analysis according to Miles & Hubberman, namely data collection, data reduction, data presentation, and data withdrawal or leveraging. The final result of the research shows that the policy of the International Tripartite Rubber Council towards Indonesia's natural rubber exports is considered ineffective. The natural rubber export policy carried out by ITRC member countries through the Agreed Export Tonnage Scheme (AETS) did not succeed in increasing the declining natural rubber price. The AETS policy reduces the volume and value of Indonesia's natural rubber exports. Other policies such as the Supply Management Scheme (SMS) have not reached the target of rejuvenating natural rubber plantations and the Demand Promotion Scheme (DPS) policy in increasing domestic natural rubber consumption is still constrained in terms of domestic technology.